Predictors of exclusive breastfeeding in the first six months: four consecutive surveys in a tertiary hospital in Lithuania - Vaidilė Jakaitė; Aurelija Peštenytė; Jolita Zakarevičienė; Vilija Sniečkuvienė; Viktorija Žitkutė; Diana Ramašauskaitė; Gintautas Domža (BMC, 2021)
Abstract Background There are little up-to-date data available on the duration of exclusive breastfeeding in Lithuania. The aim of our study was to examine the factors that could influence exclusive breastfeeding during the first 6 months of life. Methods In 2016, a survey was conducted at the Obstetrics and Gynecology Clinic of Vilnius University Hospital, Santaros Klinikos. Women in postnatal wards were opportunistically offered questionnaires and later followed up by telephone interviews at 6 weeks, 3 months, and 6 months postpartum. We used binary logistic regression to determine the factors that impacted exclusive breastfeeding during the first 6 months following childbirth. Results Of 475 eligible women that were approached, a total of 447 women were recruited, with response rates of 76.1, 71.4 and 67.0% at 6 weeks, 3 months, and 6 months postpartum, respectively. The prevalence of exclusive breastfeeding through the 6 month postpartum period was 39.8%. Exclusive breastfeeding during days 2 to 4 postpartum was positively influenced by factors such as a natural childbirth, the practice of breastfeeding on demand and maternal self-confidence in breastfeeding. Subsequently, exclusive breastfeeding on demand in the immediate postpartum period and exclusive breastfeeding for up to 3 months were associated with successful exclusive breastfeeding up to 6 months. However, the adverse factors that limited the success and duration of exclusive breastfeeding included free samples of human milk substitutes or advertising at primary healthcare centers 6 weeks after childbirth, pacifier use 6 months after childbirth, as well as amniotomy for labor induction. Conclusions Our research demonstrated that exclusive breastfeeding is impacted in both directions by a range of factors during particular periods after delivery. One of the novel findings was the adverse influence of amniotomy for labor induction on exclusive breastfeeding rates. Taking into account diverse factors influencing exclusive breastfeeding and the absence of a single way to promote it, there is a crucial need to increase the incidence of exclusive breastfeeding until infants reach the age of 6 months.